2019
DOI: 10.3389/fpsyg.2019.02862
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Return for School Refusal: A School-Based Approach Applied With Japanese Adolescents

Abstract: Cognitive behavioral therapy (CBT) is often effective in the treatment of school refusal (SR). Its usefulness is limited, however, if youth displaying SR also refuse to attend treatment sessions. In these cases parents and school staff may consider using school-based interventions that do not rely on face-to-face assessment and treatment with the young person. The current study examined the effectiveness of a school-based intervention applied in Japan to achieve rapid return to school among adolescents display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 53 publications
(88 reference statements)
1
13
0
Order By: Relevance
“…School counselors provide basic behavioral theory, outline the formation process of SAPs, highlight the negative effects of long-lasting SAPs (e.g., academic underachievement, employment difficulties, and increased risk of psychiatric illness), and propose behavioral management strategies that aim to improve school attendance (e.g., the process of flooding and coping skills for addressing resistive behaviors; Maeda, 2016;. In accordance with these consultations, Maeda and Heyne (2019) implemented the rapid school return approach, which is school-based, to 39 cases of SAPs (SR type) in Japan and reported that 28 cases (72%) resumed their normal school attendance at their original schools. However, because this study was an uncontrolled case series, further research requires case studies to evaluate the success of this type of school-based approach (Maeda & Heyne, 2019).…”
Section: Saps and School Counselors In Japanmentioning
confidence: 98%
See 4 more Smart Citations
“…School counselors provide basic behavioral theory, outline the formation process of SAPs, highlight the negative effects of long-lasting SAPs (e.g., academic underachievement, employment difficulties, and increased risk of psychiatric illness), and propose behavioral management strategies that aim to improve school attendance (e.g., the process of flooding and coping skills for addressing resistive behaviors; Maeda, 2016;. In accordance with these consultations, Maeda and Heyne (2019) implemented the rapid school return approach, which is school-based, to 39 cases of SAPs (SR type) in Japan and reported that 28 cases (72%) resumed their normal school attendance at their original schools. However, because this study was an uncontrolled case series, further research requires case studies to evaluate the success of this type of school-based approach (Maeda & Heyne, 2019).…”
Section: Saps and School Counselors In Japanmentioning
confidence: 98%
“…In accordance with these consultations, Maeda and Heyne (2019) implemented the rapid school return approach, which is school-based, to 39 cases of SAPs (SR type) in Japan and reported that 28 cases (72%) resumed their normal school attendance at their original schools. However, because this study was an uncontrolled case series, further research requires case studies to evaluate the success of this type of school-based approach (Maeda & Heyne, 2019).…”
Section: Saps and School Counselors In Japanmentioning
confidence: 99%
See 3 more Smart Citations